2014
DOI: 10.1007/s10182-014-0225-5
|View full text |Cite
|
Sign up to set email alerts
|

Testing monotonicity of pricing kernels

Abstract: International audienceThe behaviour of market agents has been extensively covered in the liter- ature. Risk averse behaviour, described by Von Neumann and Morgenstern (Theory of games and economic behavior. Princeton University Press, Princeton, 1944) via a concave utility function, is considered to be a cornerstone of classical economics. Agents prefer a fixed profit over an uncertain choice with the same expected value, however, lately there has been a lot of discussion about the empirical evidence of such r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Typically, we find either a hump-shaped PK or a U-shaped PK. Statistical significance of the local nonmonotonicity of the EPKs was initially investigated by Golubev, Ha ¨rdle, and Timofeev (2014), who test the local concavity of the utility function implied by the DAX 30 index options and the historical index returns. In a subsequent paper, Ha ¨rdle, Okhrin, and Wang (2015) build uniform confidence bands for the PK estimates and test if a decreasing PK implied by the Black-Scholes model can be fitted within the confidence corridor.…”
Section: An Overview Of the Epk Puzzle Literaturementioning
confidence: 99%
“…Typically, we find either a hump-shaped PK or a U-shaped PK. Statistical significance of the local nonmonotonicity of the EPKs was initially investigated by Golubev, Ha ¨rdle, and Timofeev (2014), who test the local concavity of the utility function implied by the DAX 30 index options and the historical index returns. In a subsequent paper, Ha ¨rdle, Okhrin, and Wang (2015) build uniform confidence bands for the PK estimates and test if a decreasing PK implied by the Black-Scholes model can be fitted within the confidence corridor.…”
Section: An Overview Of the Epk Puzzle Literaturementioning
confidence: 99%
“…Among others, the puzzle has been confirmed by Ait-Sahalia and Lo (2000) and Rosenberg and Engle (2002). Moreover, Beare and Schmidt (2016) and Golubev et al (2014) perform statistical tests and reject pricing kernel monotonicity for the S&P 500 and the German DAX, respectively. 4 In the recent past, several studies proposed possible solutions to the pricing kernel puzzle.…”
Section: Introductionmentioning
confidence: 83%
“…See, in particular, Figure 2 in [15], in which the state price density is an increasing function of the market return for monthly return levels between approximately −3% and 3%, and decreasing elsewhere. Other empirical studies of the relationship between the state price density and market returns have largely confirmed that it is often nonmonotone [16][17][18][19][20][21][22]. See also [23] for a discussion of the relevance of such nonmonotonicity for constructing density forecasts of market returns.…”
Section: Introductionmentioning
confidence: 98%